2017
DOI: 10.1002/jgm.2937
|View full text |Cite
|
Sign up to set email alerts
|

ZNF208 polymorphisms associated with ischemic stroke in a southern Chinese Han population

Abstract: Some previous studies suggested telomere length was associated with the risk of ischemic stroke (IS). The aim of this study was to further confirm the association between relative telomere length (RTL) and risk of IS and to especially explore its correlation with the risk of high-risk stroke population in southern Chinese Han. RTL was determined by using real-time quantitative polymerase chain reaction from 400 ischemic stroke patients, 409 high-risk stroke populations and 399 healthy controls. The correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Analysis further showed that the ZNF429 (36%) and ZNF208 (29%) genes had the highest frequency of mutations (Figure 2). The ZNF429 gene was reported to be significantly associated with acute postoperative pain in patients with breast cancer, while ZNF208 polymorphisms were found to be associated with ischemic stroke in a southern Chinese Han population (43,44). Research has found that PABPC1 [poly(A) binding protein cytoplasmic 1] is directly involved in the tumorigenesis of gastric cancer through its promotion of cell proliferation; consistent with this, downregulated PABPC1 expression is associated with tumor progression and a poor prognosis in colorectal cancer (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis further showed that the ZNF429 (36%) and ZNF208 (29%) genes had the highest frequency of mutations (Figure 2). The ZNF429 gene was reported to be significantly associated with acute postoperative pain in patients with breast cancer, while ZNF208 polymorphisms were found to be associated with ischemic stroke in a southern Chinese Han population (43,44). Research has found that PABPC1 [poly(A) binding protein cytoplasmic 1] is directly involved in the tumorigenesis of gastric cancer through its promotion of cell proliferation; consistent with this, downregulated PABPC1 expression is associated with tumor progression and a poor prognosis in colorectal cancer (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…We clustered similarly expressed genes to obtain four related functional disorder modules, including the four core genes Astl, Zfp472, Fmr1, and Nap1l1. Also, other studies have shown that single-nucleotide polymorphisms (SNPs) are associated with ischemic stroke, mainly affected by ZNF208 and HNF1A [27,28]. ADAMTS-4 has an antiinflammatory effect mainly in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MSUT2 knockout has anti-inflammatory and neuroprotective effects in a mouse model. The flowchart is Frankel et al, 1987;Wolfe et al, 2000;Schefe et al, 2006;Brayer et al, 2008;Town et al, 2009;Fan et al, 2012;Shi et al, 2013;Yuan et al, 2013;Xu et al, 2016;Yu et al, 2017;Brahmachari et al, 2019;Kruszka et al, 2019;Lorsch et al, 2019;Ohkubo et al, 2019;Zhang et al, 2019;Choi et al, 2020;Deshpande et al, 2020;Hu et al, 2020;Xiao et al, 2020;Dentici et shown in Figure 1. Loss of function of MSUT2 can reduce the formation of tau protein and protect the loss of neurons, but the molecular mechanism is still unclear.…”
Section: Alzheimermentioning
confidence: 99%